Comparison of the rapid methods for screening of group a rotavirus in stool samples - Pattara Khamrin (2018)
In this study, the sensitivity and specificity of three immunochromatography (IC) test kits for rapid detection of group A rotavirus were compared and evaluated with stool samples collected from children, who suffered from acute gastroenteritis during February to June, 2009 in Japan. A total of 86 stool samples were tested and compared with a reference RT-PCR method. The sensitivity among IP-Rota V, Dipstick Eiken ROTA and ROTA-ADENO test kits were 97.2, 95.8 and 88.7%, while the specificity were 100, 93.3 and 100%, respectively. It was demonstrated that the IC kits evaluated in this study could be used as an alternative method for the rapid screening of group A rotavirus in fecal specimens, especially during acute gastroenteritis outbreak season. © The Author [2010]. Published by Oxford University Press. All rights reserved.